2012
DOI: 10.1111/j.1744-7429.2012.00867.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Habitat Association and Edaphic Conditions on Tree Mortality during El Niño‐induced Drought in a Bornean Dipterocarp Forest

Abstract: The effects of El Niño-induced droughts on dipterocarp forests must be quantified to evaluate the implications of future global climatic changes for the tropical forests of Southeast Asia. We studied the mortality of trees ! 1 cm in diameter in a lowland dipterocarp forest in Borneo before, during, and after the 1997/1998 El Niño drought. The annual mortality rates were 1.30, 1.75, and 1.66 percent/yr for the pre-drought, drought, and post-drought periods, respectively. The effect of drought was tree size-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 39 publications
(124 reference statements)
3
57
2
Order By: Relevance
“…There was also a direct negative effect of fertility on survival, possibly related to soil moisture rather than soil nutrient status. Previous studies have shown that trees growing in wetter habitats in aseasonal rainforests suffer more during occasional intense droughts (Itoh et al ., ; Zuleta et al ., ). Mortality in wetter habitats at Lambir was increased significantly following the 1997–8 ENSO (Table ; Nakagawa et al ., ; Itoh et al ., ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There was also a direct negative effect of fertility on survival, possibly related to soil moisture rather than soil nutrient status. Previous studies have shown that trees growing in wetter habitats in aseasonal rainforests suffer more during occasional intense droughts (Itoh et al ., ; Zuleta et al ., ). Mortality in wetter habitats at Lambir was increased significantly following the 1997–8 ENSO (Table ; Nakagawa et al ., ; Itoh et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that trees growing in wetter habitats in aseasonal rainforests suffer more during occasional intense droughts (Itoh et al ., ; Zuleta et al ., ). Mortality in wetter habitats at Lambir was increased significantly following the 1997–8 ENSO (Table ; Nakagawa et al ., ; Itoh et al ., ). The direct effect of fertility on mortality may reflect a lack of drought resistance in trees predominating in the wetter habitats.…”
Section: Discussionmentioning
confidence: 98%
“…This drought increased community level mortality rate for lowland tropical rain forests (Aiba and Kitayama 2002;Potts 2003). Especially, Dipterocarpaceae were vulnerable to the drought event (Nakagawa et al 2000;Itoh et al 2012). Similar mortality rates might suggest a higher background mortality rate (mortality in the period without droughts) of trees in the logged forest than those in the primary forest.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is most common for ecologists to report confidence intervals for mortality rates as if they knew nothing but k and n, under the assumption of constant probability of survival either by using different analytical approximations to the binomial distribution (Condit et al, 2006(Condit et al, , 1995Condit, Hubbell, & Foster, 1993;Davies, 2001;Gilbert, Wright, Muller-Landau, Kitajima, & Hernández, 2006;Itoh et al, 2012;King, Davies, & Noor, 2006;Lewis et al, 2004;Nepstad, Tohver, Ray, Moutinho, & Cardinot, 2007;Queenborough, Burslem, Garwood, & Valencia, 2007;Welden, Hewett, Hubbell, & Foster, 1991) or by bootstrapping the binary observations directly (van Breugel et al, 2011;Thomas et al, 2013). However, it is most common for ecologists to report confidence intervals for mortality rates as if they knew nothing but k and n, under the assumption of constant probability of survival either by using different analytical approximations to the binomial distribution (Condit et al, 2006(Condit et al, , 1995Condit, Hubbell, & Foster, 1993;Davies, 2001;Gilbert, Wright, Muller-Landau, Kitajima, & Hernández, 2006;Itoh et al, 2012;King, Davies, & Noor, 2006;Lewis et al, 2004;Nepstad, Tohver, Ray, Moutinho, & Cardinot, 2007;Queenborough, Burslem, Garwood, & Valencia, 2007;Welden, Hewett, Hubbell, & Foster, 1991) or by bootstrapping the binary observations directly (van Breugel et al, 2011;Thomas et al, 2013).…”
Section: We Know That the Probability Of Survival Is Not Constant mentioning
confidence: 99%